The role of educational science in environmental management and green technology adoption in rural revitalization through interview-based insights - Chunlin Qi (Scientific Reports)
Abstract This study examines the role of educational science in rural environmental management, focusing on its contribution to the adoption of green technologies and exploring how these innovations can drive rural revitalization and advance dual-carbon objectives. The research involved qualitative interviews with 30 stakeholders, including primary and secondary school teachers, environmental protection practitioners working in rural areas, village administrators, and local residents from four rural villages in central China. The findings highlight the significant impact of education on environmental awareness and behavioral norms among rural residents, although its practical application remains constrained. Respondents emphasized the importance of aligning educational content more closely with rural realities, especially in relation to persistent pollutants, green agriculture, energy conservation, and emission reduction. Despite the potential for education to promote environmentally friendly technologies, significant barriers include the lack of instructional resources, high costs, and limited support from local residents. The study advocates for a holistic approach to promoting green technologies, which includes the development of tailored educational policies, the enhancement of teacher training in environmental education, and the alignment of educational content with rural revitalization and dual-carbon objectives. Future research may explore how sustainable environmental education might help communities navigate the tension between financial constraints and environmental targets.